To infect or not to infect: molecular determinants of bacterial outer membrane vesicle internalization by host membranes. Issue 4 (14th February 2020) - Jefferies, Damien; Khalid, Syma
Abstract: Outer membrane vesicles (OMVs) are spherical liposomes that are secreted by almost all forms of Gram-negative bacteria. The nanospheres contribute to bacterial pathogenesis by trafficking molecular cargo from bacterial membranes to target cells at the host-pathogen interface. We have simulated the interaction of OMVs with host cell membranes to understand why OMV uptake depends on the length of constituent lipopolysaccharide macromolecules. Using coarse-grained molecular dynamics simulations, we show that lipopolysaccharide lipid length affects OMV shape at the host-pathogen interface: OMVs with long (smooth-type) lipopolysaccharide lipids retain their spherical shape when they interact with host cell membranes, whereas OMVs with shorter (rough-type) lipopolysaccharide lipids distort and spread over the host membrane surface. In addition, we show that OMVs preferentially coordinate domain-favoring ganglioside lipids within host membranes to enhance curvature and affect the local lipid composition. We predict that these differences in shape preservation affect OMV internalization on long timescales: spherical nanoparticles tend to be completely enveloped by host membranes, whereas low sphericity nanoparticles tend to remain on the surface of cells. Graphical abstract: Image 1 Highlights: Smooth outer membrane vesicles (OMV) have little interaction with phospholipid bilayers. Smooth OMVs interact with domain-forming lipids in plasma membranes. Gangliosides facilitate deformation of plasma membranes around smooth OMVs. Rough OMVs deform when interacting with simple phospholipid bilayers.